A case presenting with a major depressive episode with palilalia and difficulty opening eyes as prodromal symptoms of progressive supranuclear palsy. Issue 2 (22nd June 2022) - Matsuzawa, Koji; Yokoyama, Yuichi; Watanabe, Yuichiro; Wakasugi, Takahiro; Someya, Toshiyuki
Abstract: Background: Progressive supranuclear palsy (PSP) is a neurodegenerative disease and patients with PSP frequently experience depression. However, there have been few reports of patients with major depressive disorder as an antecedent diagnosis of PSP. Here, we report a case who presented with a major depressive episode with palilalia and difficulty in opening his eyes as prodromal symptoms of PSP. Case Presentation: A Japanese man developed his first major depressive episode at the age of 75 years. At 76 years old, the patient developed palilalia and difficulty in opening his eyes, which worsened with anxiety and agitation. His depression symptoms were not alleviated following treatment with several antidepressants. He gradually became less depressed but more apathetic. Subsequently, he experienced falls and developed nuchal and axial rigidity. Magnetic resonance imaging and 123 I‐ioflupane single‐photon emission tomography showed predominant midbrain atrophy and postsynaptic striatal dopaminergic degeneration, respectively. He was diagnosed as having symptoms suggestive of PSP at the age of 80 years. The combination of sertraline and aripiprazole reduced his anxiety and agitation. Botulinum toxin treatment provided partial relief for his difficulty in eye opening. Conclusion: Some patients, such as the current case, develop a major depressive episode at the onset of PSP and present to a psychiatrist. Psychiatrists should therefore be aware of the possibility of a major depressive episode with non‐specific symptoms preceding the onset of the core clinical features of PSP. Abstract : The patient's first major depressive episode occurred at the age of 75 years. At the age of 80 years, the patient was diagnosed as having symptoms suggestive of progressive supranuclear palsy with predominant postural instability.